20g-1(-8g-15)=3(4g-5)

Simple and best practice solution for 20g-1(-8g-15)=3(4g-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20g-1(-8g-15)=3(4g-5) equation:



20g-1(-8g-15)=3(4g-5)
We move all terms to the left:
20g-1(-8g-15)-(3(4g-5))=0
We calculate terms in parentheses: -(3(4g-5)), so:
3(4g-5)
We multiply parentheses
12g-15
Back to the equation:
-(12g-15)
We get rid of parentheses
20g-1(-8g-15)-12g+15=0
We add all the numbers together, and all the variables
8g-1(-8g-15)+15=0
We move all terms containing g to the left, all other terms to the right
8g-1(-8g-15)=-15

See similar equations:

| 111/4=13-4.5s | | 21x-11x=40 | | 27=1/5r+2 | | 8c+19c+–20c−–19=–16 | | 5-4r=41 | | y+1/2=20 | | (3w−8)−4=(2w+3) | | -8t+3=-7-9t | | -8t+3=-7-9 | | 4y+3y-2=14 | | 31x-3=6x+2 | | 5f=6f-3 | | 5y+5=6y+8 | | 4t+5t=8t | | 31x-3=6x+12 | | 1.5x-3=63 | | 2x-5=x+8+x+6 | | 10^3x=27 | | x2+5xx2+5x−24=0x2+5x-24=0 | | 4y+56=14y-44 | | 12x–9=4x+15​ | | -7(6x-7)=35 | | -4.75-8.9-2.46j=9.125 | | 19x+9=18x+29 | |  50.25x-300-20.75x=508.25 | | 21x-89=4x+200 | | 14=x(7) | | 3.45x5.8=20.21 | | k-8=14.03 | | 10^x=0•001 | | 5x+4x+3x-2x+x+7=15 | | x^2+(x-1)^2=5^2 |

Equations solver categories